The influence of nanostructured UV‐blockers on mechanical properties of carbon fiber epoxy composites during accelerated weathering condition. (7th December 2017) - Pakravan, Hamid Reza; Yari, Hossein
Abstract : In a 3‐stage experimental approach, it was attempted to enhance the weathering performance of carbon fiber reinforced epoxy composites (CFRC). For this purpose, 2 types of UV‐blocking nanoparticles titanium dioxide (TiO2 ) and zinc oxide (ZnO) were employed to separately be introduced into the composite matrix. In the first stage, the optimum content of nanoparticles was found to be 0.5 wt.% for both nanoparticles. The second stage of experiments revealed that addition of nanoparticles into CFRC could increase the strength of the composite around 6% to 12% depending on the nanoparticles used. In the third stage (weathering), it was demonstrated that nanoparticles significantly enhanced the weathering stability of CFRC. Finally, it was concluded that while TiO2 could reinforce the composite more efficiently, ZnO nanoparticles provided a higher level of protection (62% improvement in weathering stability compared with neat composite). The higher protection efficiency of ZnO compared with TiO2 was explained by its lower photocatalytic activity during weathering.